Frequency of Low Levels of High Density Lipoprotein Cholesterol in Newly Diagnosed Patients of Acute Coronary Syndrome - Nasim, Zain; Abbas, Shahid (Indus Journal of Bioscience Research, 2025)
Background: One of the most significant causes of worldwide morbidity and mortality is acute coronary syndrome (ACS). One cardiovascular risk factor that is under-acknowledged, yet is significant, is dyslipidemia, specifically the low high-density lipoprotein cholesterol (HDL-C). Aim: To identify how often low HDL-C occurred in newly diagnosed ACS patients and how it is related to clinical risk factors. Methodology: It was a cross-sectional study that was carried out in the Faisalabad Institute of Cardiology between August 2021 and February 2022. The patient population of ACS was 125 with the age group 18-70. The amount of HDL-C was measured and analysed using SPSS. A critical p-value was set to be 0.05. Findings: There were 83.2% men and a mean age of 44.35 ± 9.69 years. 18.4% of patients had low HDL-C. Significant associations were seen with smoking (p=0.031) and hypertension (p=0.0009). Conclusion: HDL-C is a large and modifiable risk factor of ACS patients. Early intervention and screening are suggested.